Spherical-flower-like mordenite as well as preparation method and application thereof
By forming a lamellar structure of floral-like mordenite, the problem of poor diffusion channels of nanomaterials in the prior art is solved, and efficient diffusion and catalytic conversion of fused-ring aromatic hydrocarbons are achieved.
Patent Information
- Application Number
- CN202311403959.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, the bulk agglomerated nanomaterials have a single exposed crystal surface and insufficient exposure of effective orifices, resulting in slow diffusion speed of raw material molecules and poor diffusion channels, making it difficult to effectively treat heavy fused-cyclic aromatic hydrocarbons.
By self-assembly forming a floral spherical mordenite, multiple sheet mordenites are cross-aggregated in an upright shape, forming a sheet structure with cross-arrangement of multiple angles, increasing the exposure of effective orifices and the smoothness of diffusion channels.
It improves the diffusion performance and catalytic activity of the fused ring aromatic hydrocarbon raw materials, enhances acid contactability, and is suitable for use in the lightweight conversion production BTX reaction process.
Smart Images

Figure CN119898789A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of mordenite, and in particular relates to a flower ball-like mordenite and a preparation method and application thereof. Background Art
[0002] Microporous molecular sieve materials are one of the most important solid acid catalytic materials in the petrochemical industry. The active acid sites used for catalysis are distributed inside and outside the unique pores of the molecular sieve. Their accessibility plays a decisive role in the selection of reactions, the degree of reaction, and the direction of the reaction path. As an important member of them and an important component of acidic catalysts, mordenite plays an important conversion function in the petrochemical field. Mordenite is an aluminosilicate crystal with a two-dimensional layered pore structure. It has twelve-membered ring (0.65×0.7nm) pores and eight-membered ring (0.26×0.57nm) straight pores extending parallel to the c-axis direction, and eight-membered ring (0.34×0.48nm) straight pores extending parallel to the b-axis direction. Due to the uniqueness of its pore system, it is often used in the conversion of aromatics, especially heavy aromatics. Heavy aromatics are by-products of petroleum processing. People usually refer to carbon nine aromatics (C9A) and carbon ten aromatics (C 10 A) and heavy aromatic hydrocarbons with carbon 11 or above (C 11 + A) are collectively referred to as heavy aromatics. Petroleum heavy aromatics mainly come from catalytic cracking, catalytic reforming units and naphtha steam cracking units, with huge output. In the traditional petrochemical industry, heavy aromatics are mainly used to blend gasoline and diesel components, playing the role of fossil fuels. However, with the development trend of oil product upgrading, the content of heavy aromatics in oil products is required to be further reduced. How to convert this part of extruded heavy aromatics is a key technical issue facing the future refining industry. Common heavy aromatic conversion and utilization focuses on the research on its light-weight preparation of light aromatics. The LCO conversion technology (LCO-X) developed by UOP for polycyclic aromatics belongs to this type of technology, while the heavy component conversion technology for catalytic reforming is mainly completed through the lightening and disproportionation of heavy aromatics and alkyl transfer units. For example, the TAC9 developed by UOP is suitable for processing pure C9A / C 10A aromatics, and TA series alkyl transfer catalysts are suitable for processing raw materials containing a certain amount of monocyclic heavy aromatics, but the above catalysts have certain restrictions on the content of polycyclic aromatics in the raw materials, and the conversion efficiency of the catalysts for heavy aromatics is also low. At present, there is no industrial report on the treatment of all components of heavy aromatics in catalytic reforming. The lightening of heavy aromatics mainly involves the selective hydrogenation of polycyclic aromatics, the cracking and dealkylation of monocyclic aromatics, among which acidic molecular sieves are the key materials to realize this process. For the lightening reaction of polycyclic aromatics, the pore structure on the catalyst has an important influence on the diffusion and conversion of the reactants. First, only when the molecular size is smaller than the pore diameter can it freely enter and exit and reach the acidic site for catalytic conversion; secondly, the length of the molecular sieve pore has a significant effect on the diffusion of raw material and product molecules. In order to weaken the diffusion limitation of micropores as much as possible, improve product selectivity, and increase catalyst life, it can be achieved by building a multi-level pore molecular sieve pore system containing mesopores and micropores, that is, by enhancing the diffusion of reaction substrates and products. Synthesizing nano-sized molecular sieves is an important way to achieve diffusion enhancement.
[0003] The morphology of mordenite is generally a rod-shaped crystal with a regular geometric shape. The morphology of mordenite can be controlled by adjusting the synthesis conditions, the synthesis method or introducing a special structure-directing agent, thereby changing the pore structure and catalytic performance. Zhang Kun et al. (CN102718231A) used hexadecyltrimethyl-p-toluenesulfonic acid as a structure-directing agent to synthesize a small-grained layered nano-mordenite with a sheet thickness of about 50nm. Shen Wenjie et al. (CN107963637A) used specially designed hexadecyl N-dimethylethyl-N, N-dimethylammonium bromide as a template to synthesize a sheet-like mordenite oriented with the c-axis. Qi Xiaolan et al. (CN102190316A) synthesized a mordenite molecular sieve with a microporous-mesoporous composite pore structure under hydrothermal conditions using an organic amine structure-directing agent method. Xing Shujian et al. (CN1847046A) added seed crystals, used sodium chloride or sodium sulfate metal salts as additives, aged at 100°C, and then hydrothermally crystallized at 130-150°C to obtain spherical aggregates of mordenite with an average size of 42-90nm. Hao Qingqing et al. (CN106517239A) synthesized swellable layered mordenite molecular sieves using hexamethyleneimine as a template. The flaky molecular sieves synthesized by many scholars have better catalytic performance than traditional mordenite. It can be seen that the catalytic performance of this type of flaky molecular sieve is far superior to the blocky MOR molecular sieve synthesized by traditional methods, and has broad application prospects in the field of catalysis. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the existing block-shaped agglomerated nanomaterials in the prior art, such as strips, disks and spheres, have defects in practical applications, such as insufficient exposure of effective pores, slow diffusion of raw material molecules and blocked diffusion channels due to the single exposed crystal face, resulting in the problem that the diffusion performance is not suitable for processing heavy condensed aromatic hydrocarbon raw materials. The present invention provides a flower ball-like mordenite and a preparation method and application thereof, wherein the flower ball-like mordenite is a self-assembled aggregate of multiple sheet-like mordenites, wherein the multiple sheet-like mordenites are cross-aggregated in an upright shape for the self-assembly. The present invention utilizes the sufficient exposure of the effective pores by the cross-structure of the nanosheets to better solve the above-mentioned problems, and is used for the reaction of converting condensed aromatic hydrocarbons to produce light aromatic hydrocarbons, has the advantages of high reaction activity and selectivity, and can be used in the industrial production of aromatic hydrocarbon conversion.
[0005] On one hand, the present invention provides a flower ball-like mordenite, which is a self-assembled aggregate of multiple sheet-like mordenites, wherein the multiple sheet-like mordenites are vertically cross-aggregated with each other for the self-assembly, and the 001 crystal plane corresponding to the 12-membered pore of the sheet-like mordenite is exposed to the outside.
[0006] The thickness of the flake-like mordenite is 2-200 nm, preferably 5-100 nm.
[0007] The diameter of the flower-spherical mordenite is 1000-6000 nm, preferably 1200-5000 nm.
[0008] The mesopore diameter of the flower-like mordenite is 3 to 200 nm, and the mesopore volume is 0.05 to 0.9 cm 3 / g; Preferably, the mesopore diameter of the flower-like mordenite is 10-20 nm, and the mesopore volume is 0.1-0.6 cm 3 / g; More preferably, the ratio of the mesopore volume to the total pore volume of the flower ball-like mordenite is 40% to 80%.
[0009] The specific surface area of the flower-like mordenite is 320 to 865 m 2 / g, external specific surface area 70~610m 2 / g.
[0010] The second aspect of the present invention is to provide a method for preparing a flower-spherical mordenite, which is preferably used to prepare the flower-spherical mordenite described in the first aspect, and the preparation method comprises: (1) mixing an aluminum source, a structure directing agent 1, an alkali source and water to obtain a mixed system 1; (2) adding a silicon source and a structure directing agent 2 to the mixed system 1, and mixing to obtain a mixed system 2; (3) stirring and crystallizing the mixed system 2, and filtering and washing to obtain a crystallized product; (4) performing ion exchange and heat treatment on the crystallized product to obtain the flower-spherical mordenite.
[0011] The aluminum source is selected from one or more of boehmite, pseudo-boehmite, aluminum hydroxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum isopropoxide; and / or, the silicon source is selected from one or more of silicon oxide, water glass, silica sol, ethyl silicate, sodium silicate, silica gel, and white carbon black; and / or, the alkali source is selected from at least one of sodium hydroxide, liquid caustic soda, potassium hydroxide, and calcium hydroxide.
[0012] The structure directing agent is selected from aliphatic amine compounds, preferably one or more selected from linear alkylamines, tetraalkylammonium hydroxides, tetraalkylammonium halides, ammonia water, cyclic alkylamines, and alkyl diammonium halides, and more preferably one or more selected from ethylamine, hexylamine, ethylenediamine, hexyldiamine, tetraethylammonium bromide, tetraethylammonium hydroxide, tetramethylammonium bromide, tetramethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium hydroxide, ammonia water, hexamethyleneimine, cyclohexylamine, and hexamethylammonium bromide.
[0013] The second structure directing agent is selected from: a compound containing at least one benzene ring and at least one amino group, and / or a compound containing at least one benzene ring and at least one quaternary ammonium salt;
[0014] Preferably, the second structure directing agent is selected from at least one of the compounds represented by formula (I) and / or the compounds represented by formula (II):
[0015]
[0016] In formula (I), R1 to R7 are each independently selected from hydrogen, alkyl or aryl, and n is any natural number. Preferably, R1 to R7 are each independently selected from hydrogen, C1 to C10 alkyl or benzyl, and n is a natural number of 0 to 10;
[0017]
[0018] In formula (II), R 1 ~R 10 Each is independently selected from hydrogen, alkyl or aryl, and m is any natural number; M - is an anion; preferably, R 1 ~R10 Each is independently selected from hydrogen, C1-C10 alkyl or benzyl, m is any natural number from 0 to 10; M - Cl - Br - ,I - 、F - or OH - ;
[0019] More preferably, the second structure-directing agent represented by formula (I) is selected from at least one of aniline, methylaniline, dimethylaniline, trimethylaniline, tetramethylaniline, pentamethylaniline, o-ethylaniline, p-ethylaniline, m-ethylaniline, isopropylbenzylamine, benzyldimethylamine, N-benzyltert-butylamine, N-benzyln-butylamine, N-benzylisobutylamine and N-benzylisobutylamine; and / or, the second structure-directing agent represented by formula (II) is selected from at least one of benzyltriethylammonium chloride, benzyltriethylammonium bromide, benzyltriethylammonium chloride, benzyltriethylammonium bromide and benzyltriethylammonium chloride. At least one of ethylammonium fluoride, benzyltriethylammonium hydroxide, benzyltripropylammonium chloride, benzyltripropylammonium bromide, benzyltripropylammonium fluoride, benzyltripropylammonium hydroxide, tetradecyldimethylbenzylammonium bromide, hexadecyldimethylbenzylammonium bromide, dodecyldimethylbenzylammonium bromide, decyldimethylbenzylammonium bromide, decyldimethylbenzylammonium chloride, tetradecyldimethylbenzylammonium chloride, hexadecyldimethylbenzylammonium chloride, and dodecyldimethylbenzylammonium chloride.
[0020] The molar ratio of the structure directing agent 1 to the silicon source is 0.001-0.5, the molar ratio of the water to the silicon source is 5-1000 (preferably 5-150), the molar ratio of the alkali source to the silicon source is 0.005-0.5, the molar ratio of the silicon source to the aluminum source is 5-60, and the molar ratio of the structure directing agent 2 to the silicon source is 0.0005-0.5, wherein the molar amount of the aluminum source is calculated as the molar amount of its Al2O3, the molar amount of the alkali source is calculated as the molar amount of its metal oxide (M2O), and the molar amount of the silicon source is calculated as SiO2.
[0021] Step (3) is carried out in an autogenous pressure crystallization reactor. Preferably, the stirring is carried out for 2 to 8 hours; and / or, in step (3), the crystallization temperature is 130 to 200° C., and the crystallization time is 1 to 48 hours.
[0022] The third aspect of the present invention is to provide a flower ball-like mordenite obtained by the preparation method described in the second aspect of the present invention.
[0023] The fourth aspect of the present invention is to provide a zeolite catalyst, which includes mordenite, a binder and a metal component, wherein the mordenite is selected from the flower-ball-like mordenite described in the first aspect of the present invention or the flower-ball-like mordenite obtained by the preparation method described in the second aspect of the present invention; preferably, the binder is selected from at least one of silica sol, aluminum sol, phosphate aluminum sol, alumina, and pseudo-boehmite; and / or the metal component is selected from at least one or at least two of platinum, molybdenum, bismuth, tin, cadmium, cobalt, nickel, rhenium, palladium, gallium, ruthenium, and lanthanum.
[0024] The fifth aspect of the present invention is to provide the use of the flower-like mordenite described in the first aspect of the present invention, the flower-like mordenite obtained by the preparation method described in the second aspect of the present invention, or the zeolite catalyst described in the fourth aspect of the present invention in the aromatic hydrocarbon transalkylation reaction, especially in the conversion of C6 to C12 aromatic hydrocarbons to produce xylene.
[0025] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0026] Compared with the prior art, the present invention has the following beneficial effects: the flower-like mordenite has a multi-angle cross-arrangement due to its lamellar structure, which makes the crystal surface and effective pores more fully exposed. In particular, the diffusion channels constructed by the cross-particles between different lamellar layers are conducive to the diffusion of condensed aromatic hydrocarbon raw material molecules and shorten the diffusion range; the higher ratio of the external surface acid content to the total acid content reflects the enhancement of acid contactability, which helps the condensed aromatic hydrocarbon raw material molecules to contact with the acidic sites and undergo conversion, and is suitable for the reaction process of increasing the production of BTX in the conversion of inferior aromatic hydrocarbons, especially condensed aromatic hydrocarbons to light weight. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The SEM image of the mordenite obtained in Example 1 is shown;
[0028] Figure 2 The SEM images of the mordenite obtained at different magnifications in Example 1 are shown;
[0029] Figure 3 A TEM image of the mordenite obtained in Example 1 is shown.
[0030] Figure 4 The XRD pattern of the mordenite obtained in Example 1 is shown. DETAILED DESCRIPTION
[0031] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.
[0032] One of the purposes of the present invention is to provide a flower ball-like mordenite, which is a self-assembled aggregate of multiple sheet-like mordenites, wherein the multiple sheet-like mordenites are vertically cross-aggregated with each other for the self-assembly, and the 001 crystal plane corresponding to the 12-membered pore of the sheet-like mordenite is exposed to the outside.
[0033] Among them, heavy aromatics and naphthalene series can only enter the pores through the 12-membered ring due to their large size, and cannot enter the 8-membered ring. Therefore, the 12-membered ring pores are exposed to the outside, which can promote large-sized raw material molecules to enter the acidic sites in the pores for reaction.
[0034] The flower-spherical mordenite of the present invention has a MOR topological structure.
[0035] In a preferred embodiment, the thickness of the sheet-like mordenite is 2 to 200 nm, preferably 5 to 100 nm, more preferably 5 to 30 nm, for example 2 nm, 5 nm, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm or 200 nm.
[0036] In a preferred embodiment, the diameter of the flower ball-like mordenite is 1000-6000 nm, preferably 1200-5000 nm, more preferably 3000-4000 nm, for example 1000 nm, 2000 nm, 3000 nm, 4000 nm, 5000 nm or 6000 nm.
[0037] In a further preferred embodiment, the ratio of the diameter of the flower ball-like mordenite to the thickness of the sheet is 30-300, preferably 80-200, for example 30, 50, 80, 100, 120, 150, 180, 200, 220, 250, 280 or 300.
[0038] In a preferred embodiment, the mesopore diameter of the flower-like mordenite is 3 to 200 nm, and the mesopore volume is 0.05 to 0.9 cm 3 / g.
[0039] For example, the mesopore diameter of the flower ball-like mordenite is 3 nm, 5 nm, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm or 200 nm, and the mesopore volume is 0.05 cm 3 / g, 0.08cm 3 / g, 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g or 0.9cm 3 / g.
[0040] In a further preferred embodiment, the mesopore diameter of the flower ball-like mordenite is 10-20 nm, and the mesopore volume is 0.1-0.6 cm 3 / g.
[0041] For example, the mesopore diameter of the flower-like mordenite is 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm, and the mesopore volume is 0.1 cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g or 0.6cm 3 / g.
[0042] In a further preferred embodiment, the ratio of the mesopore volume to the total pore volume of the spherical mordenite is 40% to 80%, preferably 50 to 70%, for example 40%, 50%, 60%, 70% or 80%.
[0043] In a preferred embodiment, the specific surface area of the flower-like mordenite is 320 to 865 m 2 / g, external specific surface area 70~610m 2 / g, for example, 320m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g、600m 2 / g, 650m 2 / g、700m 2 / g, 750m 2 / g、800m 2 / g, 850m 2 / g or 865m 2 / g.
[0044] In a further preferred embodiment, the ratio of the external specific surface area to the total specific surface area is 20% to 60%, preferably 30% to 50%, for example 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%.
[0045] In the present invention, the flower ball-like mordenite has a multi-angle cross-arrangement due to its lamellar structure, which exposes the crystal surface and effective pores more fully. In particular, the diffusion channels built by the cross-particles between different lamellar layers are conducive to the diffusion of condensed aromatic hydrocarbon raw material molecules and shorten the diffusion range; the higher ratio of the external surface acid content to the total acid content reflects the enhancement of acid contactability, which helps the condensed aromatic hydrocarbon raw material molecules to contact with the acidic site and undergo conversion, and is suitable for the reaction process of increasing the production of BTX in the conversion of inferior aromatic hydrocarbons, especially condensed aromatic hydrocarbons to light weight.
[0046] The second object of the present invention is to provide a method for preparing a flower-spherical mordenite, preferably for preparing the flower-spherical mordenite described in one of the objects of the present invention, the preparation method comprising:
[0047] (1) mixing an aluminum source, a structure directing agent 1, an alkali source and water to obtain a mixed system 1;
[0048] (2) adding a silicon source and a structure directing agent 2 to the mixture 1, and mixing to obtain a mixed system 2;
[0049] (3) stirring and crystallizing the mixed system 2, and filtering and washing to obtain a crystallized product;
[0050] (4) performing ion exchange and heat treatment on the crystallized product to obtain the flower ball-like mordenite.
[0051] In a preferred embodiment, the aluminum source is selected from one or more of boehmite, pseudo-boehmite, aluminum hydroxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum isopropoxide.
[0052] In a preferred embodiment, the silicon source is selected from one or more of silicon oxide, water glass, silica sol, ethyl silicate, sodium silicate, silica gel, and white carbon black.
[0053] In a preferred embodiment, the alkali source is selected from at least one of sodium hydroxide, liquid caustic soda, potassium hydroxide and calcium hydroxide.
[0054] In a preferred embodiment, the structure directing agent is selected from aliphatic amine compounds, preferably one or more selected from linear alkylamines, tetraalkylammonium hydroxides, tetraalkylammonium halides, ammonia water, cyclic alkylamines, and alkyl diammonium halides.
[0055] In a further preferred embodiment, the structure directing agent is selected from one or more of ethylamine, hexylamine, ethylenediamine, hexyldiamine, tetraethylammonium bromide, tetraethylammonium hydroxide, tetramethylammonium bromide, tetramethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium hydroxide, ammonia water, hexamethyleneimine, cyclohexylamine, and hexamethylammonium bromide (HMBr2).
[0056] In a preferred embodiment, the second structure directing agent is selected from: a compound containing at least one benzene ring and at least one amino group, and / or a compound containing at least one benzene ring and at least one quaternary ammonium salt.
[0057] In the present invention, the role of the second structure directing agent is not to serve as a template, but to mainly play a role in morphology control. Specifically, it mainly inhibits growth after the benzene ring adsorbs on the
[001] crystal plane, resulting in inhibition of C-axis growth and promotion of flake formation. This is mainly achieved through organic amines with benzene rings. Through the π-π coupling of the benzyl ring on the benzylamine, the large π bond interacts with the silicon hydroxyl group to achieve the effect of crystal plane orientation control.
[0058] In a further preferred embodiment, the second structure directing agent is selected from at least one of the compounds represented by formula (I) and / or the compounds represented by formula (II):
[0059]
[0060] In formula (I), R1 to R7 are each independently selected from hydrogen, alkyl or aryl, and n is any natural number. Preferably, R1 to R7 are each independently selected from hydrogen, C1 to C10 alkyl or benzyl, and n is a natural number of 0 to 10;
[0061]
[0062] In formula (II), R 1 ~R 10 Each is independently selected from hydrogen, alkyl or aryl, and m is any natural number; M - is an anion; preferably, R 1 ~R 10 Each is independently selected from hydrogen, C1-C10 alkyl or benzyl, m is any natural number from 0 to 10; M - Cl - Br - ,I - 、F- or OH - .
[0063] In a further preferred embodiment, the structure directing agent 2 represented by formula (I) is selected from at least one of aniline, methylaniline, dimethylaniline, trimethylaniline, tetramethylaniline, pentamethylaniline, o-ethylaniline, p-ethylaniline, m-ethylaniline, isopropylbenzylamine, benzyldimethylamine, N-benzyltert-butylamine, N-benzyln-butylamine, N-benzylisobutylamine and N-benzylisobutylamine.
[0064] In a further preferred embodiment, the structure directing agent shown in formula (II) is at least one selected from benzyltriethylammonium chloride, benzyltriethylammonium bromide, benzyltriethylammonium fluoride, benzyltriethylammonium hydroxide, benzyltripropylammonium chloride, benzyltripropylammonium bromide, benzyltripropylammonium fluoride, benzyltripropylammonium hydroxide, tetradecyldimethylbenzylammonium bromide, hexadecyldimethylbenzylammonium bromide, dodecyldimethylbenzylammonium bromide, decyldimethylbenzylammonium bromide, decyldimethylbenzylammonium chloride, tetradecyldimethylbenzylammonium chloride, hexadecyldimethylbenzylammonium chloride, and dodecyldimethylbenzylammonium chloride.
[0065] Among them, the inventors found through a large number of experimental studies that the structure directing agent 2 can promote the flake-like mordenite to be in an upright state and cross each other to form the flower-like spherical mordenite.
[0066] In a preferred embodiment, the molar ratio of the structure directing agent 1 to the silicon source is 0.001-0.5, the molar ratio of the water to the silicon source is 5-1000 (preferably 5-150), the molar ratio of the alkali source to the silicon source is 0.005-0.5, the molar ratio of the silicon source to the aluminum source is 5-60, and the molar ratio of the structure directing agent 2 to the silicon source is 0.0005-0.5, wherein the molar amount of the aluminum source is calculated as the molar amount of Al2O3, the molar amount of the alkali source is calculated as the molar amount of its metal oxide (M2O), and the molar amount of the silicon source is calculated as SiO2.
[0067] For example, the molar ratio of the structure directing agent 1 to the silicon source is 0.001, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5, the molar ratio of water to the silicon source is 5, 10, 20, 50, 80, 100, 120, 150, 180, 200, 500, 800 or 1000, and the molar ratio of the alkali source to the silicon source is 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5, the molar ratio of the silicon source to the aluminum source is 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60, the molar ratio of the structure directing agent 2 to the silicon source is 0.0005, 0.001, 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5, wherein the molar amount of the alkali source is calculated as the molar amount of its metal oxide (M2O), and the molar amount of the silicon source is calculated as SiO2.
[0068] In a further preferred embodiment, the molar ratio of the structure directing agent 1 to the silicon source is 0.05-0.5, the molar ratio of the water to the silicon source is 10-100, the molar ratio of the alkali source to the silicon source is 0.05-0.3, the molar ratio of the silicon source to the aluminum source is 5-60, and the molar ratio of the structure directing agent 2 to the silicon source is 0.05-0.5, wherein the molar amount of the aluminum source is calculated as the molar amount of Al2O3, the molar amount of the alkali source is calculated as the molar amount of its metal oxide (M2O), and the molar amount of the silicon source is calculated as SiO2.
[0069] Among them, the inventors have found through a large number of experimental studies that not adding a silicon source in step (1) can promote the rapid synthesis of sheet-like mordenite. The reason for adding the silicon source later is to prevent the silicon source from being hydrolyzed in advance under alkaline conditions to form water glass, causing the system to be uneven, reducing the gelling effect, and affecting the crystallization rate. In other words, it is to ensure the uniform mixing of aluminum, alkali, and template agent.
[0070] In a preferred embodiment, in step (3), the crystallization temperature is 130 to 200° C., and the crystallization time is 1 to 48 hours.
[0071] In a further preferred embodiment, step (3) is carried out in an autogenous crystallization reactor, and preferably, the stirring is carried out for 2 to 8 hours.
[0072] In a preferred embodiment, the ion exchange in step (4) is carried out by an ion exchange method commonly used in the art, and the conditions for the ion exchange are preferably but not limited to: 0.01-10 mol / L (e.g., 0.01 mol / L, 0.1 mol / L, 1 mol / L, 2 mol / L, 4 mol / L, 6 mol / L, 8 mol / L or 10 mol / L) of at least one of ammonium nitrate solution, ammonium chloride, hydrochloric acid, sulfuric acid, ammonium sulfate and ammonium phosphate are treated at 50-120 degrees (e.g., 50 degrees, 60 degrees, 80 degrees, 100 degrees or 120 degrees) for 5-20 hours (e.g., 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours or 20 hours); specifically, 0.1 mol / L ammonium nitrate solution is treated at 95 degrees for 12 hours.
[0073] In a preferred embodiment, the heat treatment conditions in step (4) include: calcining at 400-700 degrees (for example, 400 degrees, 450 degrees, 500 degrees, 550 degrees, 600 degrees, 650 degrees or 700 degrees) in an air atmosphere for 2-10 hours (for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours); specifically, for example, calcining at 550 degrees for 6 hours in an air atmosphere.
[0074] The third object of the present invention is to provide a spherical mordenite obtained by the preparation method described in the second object of the present invention.
[0075] The fourth object of the present invention is to provide a zeolite catalyst, which comprises mordenite, a binder and a metal component, wherein the mordenite is selected from the flower-spherical mordenite described in the first object of the present invention or the flower-spherical mordenite obtained by the preparation method described in the second object of the present invention.
[0076] In a preferred embodiment, the binder is selected from at least one of silica sol, aluminum sol, phosphate aluminum sol, alumina, and pseudo-boehmite.
[0077] In a preferred embodiment, the metal component is selected from at least one or at least two of platinum, molybdenum, bismuth, tin, cadmium, cobalt, nickel, rhenium, palladium, gallium, ruthenium and lanthanum.
[0078] Wherein, the metal component precursor is a metal salt corresponding to the metal component, preferably at least one of metal nitrate, metal sulfate and metal chloride.
[0079] In a preferred embodiment, based on 100 wt% of the zeolite molecular sieve, the zeolite molecular sieve comprises: a) 3 to 98 wt% of the flower-like mordenite; b) 2 to 90 wt% of the binder; and c) 0.0001 to 20 wt% of the metal component.
[0080] For example, based on 100wt% of the zeolite molecular sieve, the zeolite molecular sieve includes: a) 3wt%, 5wt%, 10wt%, 20wt%, 40wt%, 60wt%, 80wt%, 90wt% or 98wt% of the flower-like mordenite; b) 2wt%, 5wt%, 10wt%, 20wt%, 40wt%, 60wt%, 80wt% or 90wt% of the binder; c) 0.0001wt%, 0.001wt%, 0.01wt%, 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 15wt% or 20wt% of the metal component.
[0081] In the present invention, the flower ball-like mordenite is first mixed with the binder, and then the metal component is loaded. Preferably, the flower ball-like mordenite and the binder are uniformly mixed by physical mixing means such as grinding or powdering to obtain a carrier. Preferably, the loading method is any one or more of an equal volume impregnation method, an ion exchange method, a precipitation method, and a physical grinding method to load a solution or a metal salt containing the metal component precursor on the carrier, wherein the physical grinding method and / or the equal volume impregnation method are preferred; then, the catalyst matrix is obtained after kneading, molding, and drying, and the zeolite catalyst is obtained after heat treatment.
[0082] The fifth object of the present invention is to provide the use of the flower-spherical mordenite described in the first object of the present invention, the flower-spherical mordenite obtained by the preparation method described in the second object of the present invention, or the zeolite catalyst described in the fourth object of the present invention in the aromatic hydrocarbon transalkylation reaction, especially in the conversion of C6-C12 aromatic hydrocarbons to produce xylene.
[0083] In a preferred embodiment, the aromatic hydrocarbon transalkylation reaction is carried out under a hydrogen atmosphere, the reaction temperature is 300-460°C, the reaction pressure is 2-10 MPa, the hydrogen-to-hydrocarbon molecular ratio is 0.5-20.0 mol / mol, and the feed mass space velocity is 0.5-10 h -1 .
[0084] For example, in the aromatic transalkylation reaction, the reaction temperature is 300°C, 350°C, 400°C, 450°C or 460°C, the reaction pressure is 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa or 10MPa, the hydrogen-to-hydrocarbon molecular ratio is 0.5, 0.5, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18 or 20.0 mol / mol, and the feed mass space velocity is 0.5 to 10h -1 .
[0085] In a preferred embodiment, in the aromatic hydrocarbon transalkylation reaction, the reaction raw materials include C9 and above aromatic hydrocarbons and optional naphthalene series.
[0086] In a further preferred embodiment, in the reaction raw materials, the content of C9 and above aromatic hydrocarbons is 70-100wt%, and the content of naphthalene series is 0-90wt%; preferably, the content of C9 and above aromatic hydrocarbons is higher than 85wt%, and the content of naphthalene series is 5-50wt%.
[0087] For example, in the reaction raw materials, the content of C9 and above aromatic hydrocarbons is 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt% or 100wt%, and the content of naphthalene series is 0wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%.
[0088] In the present invention, the flower ball-like mordenite has a multi-angle cross-arrangement due to its lamellar structure, which exposes the crystal surface and effective pores more fully. In particular, the diffusion channels built by the cross-particles between different lamellar layers are conducive to the diffusion of condensed aromatic hydrocarbon raw material molecules and shorten the diffusion range; the higher ratio of the external surface acid content to the total acid content reflects the enhancement of acid contactability, which helps the condensed aromatic hydrocarbon raw material molecules to contact with the acidic site and undergo conversion, and is suitable for the reaction process of increasing the production of BTX in the conversion of inferior aromatic hydrocarbons, especially condensed aromatic hydrocarbons to light weight.
[0089] Example
[0090] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0091] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0092] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0093] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0094] In the embodiment, the silica content in the white carbon black is 85wt%, the silica content in the silica gel is 90wt%, and the Al2O3 content in the alumina sol is 12wt%.
[0095] [Example]
[0096] Molecular sieve synthesis. Aluminum source, structure directing agent 1, alkali source and distilled water are mixed to obtain mixture 1, silicon source and structure directing agent 2 are added to mixture 1 and mixed evenly to obtain mixture 2, which is added to a self-generated pressure crystallization kettle and stirred vigorously for 5 hours, and then the temperature is raised to a crystallization temperature of 130-200°C, and crystallized at this temperature for 1-48 hours to complete the crystallization, and the solid phase is filtered and washed with water to obtain a crystallized product of the molecular sieve; the crystallized product is ion exchanged in a 0.5 mol / L ammonium nitrate solution at 95°C for 6 hours, and then calcined at 550°C in an air atmosphere for 6 hours to obtain Z1, Z2, Z3, and Z4 hydrogen-type molecular sieves.
[0097] Catalyst preparation: Take 50 grams of Z1, Z2, Z3, and Z4 molecular sieve powder respectively, impregnate a certain amount of ammonium heptamolybdate and ammonium chloroplatinate solution (calculated based on the Mo metal loading accounting for 2.2% of the total catalyst mass and the Pt metal loading accounting for 0.2% of the total catalyst mass), and knead it with 15 grams of alumina, dry it at 120 degrees for 4 hours, calcine it at 500 degrees for 3 hours, and reduce it under hydrogen conditions at 450 degrees for 3 hours to prepare the catalyst.
[0098] Catalyst evaluation: 10 g of catalyst was loaded into a fixed bed reactor, heated to 370°C under a hydrogen atmosphere, and 20 g of reformed C9 + (Contains C10 + 5g, naphthalene series 2g) components were passed through the reactor once, at a reaction pressure of 3.0MPa, a hydrogen-to-hydrocarbon molecular ratio of 3, a reaction temperature of 370°C, and a feed mass space velocity of 2.0h -1 The evaluation was carried out under the conditions of
[0099] The mordenite obtained in Example 1 and Example 2 was characterized by SEM (see Figure 1 and Figure 2 ), the mordenite obtained in Example 1 was characterized by TEM (see Figure 3 );Depend on Figures 1-2 It can be seen that the mordenite is formed by a plurality of sheet-like mordenite zeolites intersecting each other in an upright state, and the final aggregate is in a flower ball shape; Figure 3 It can be seen that the 001 crystal plane corresponding to the 12-membered pores of the sheet-like mordenite is exposed to the outside.
[0100] The mordenite obtained in Example 1 was subjected to XRD detection, and the results were as follows: Figure 4 As shown, it has a MOR structure.
[0101] [Comparative Example 1]
[0102] The process of Example 1 was repeated, except that an equal amount of structure directing agent 1 was used to replace structure directing agent 2, and other conditions remained unchanged. Result No lamellar structure was formed.
[0103] [Comparative Example 2]
[0104] The process of Example 1 was repeated, except that the silicon source was equally divided into two parts, one of which was added to mixture 1 and the other was added to mixture 2, and other conditions remained unchanged. The crystallization process was affected, and the particles were too large and had no lamellar structure.
[0105] [Comparative Example 3]
[0106] The process of Example 1 was repeated, except that the benzyl template agent was reduced. In Comparative Example 3, there were flakes but the thickness was too large.
[0107] Table 1. Conditions of Examples 1 to 4 and Comparative Examples 1 to 3
[0108]
[0109] Table 2. Structure of molecular sieve products
[0110]
[0111] The larger the ratio of the aggregate diameter to the lamella thickness, the thinner the lamella. The aggregate refers to the obtained flower-like mordenite.
[0112] Table 3. Comparison of catalyst performance
[0113]
[0114]
[0115] By comparison, it can be seen that the inventive example shows a higher conversion rate of heavy aromatics than the corresponding example, especially the C10+ conversion rate and the light conversion rate of naphthalene series, and also promotes the selectivity of xylene in the product. Thanks to its open pore structure, the smaller the thickness of the sheet, the more it can promote the diffusion of macromolecular substrates, indicating that the sheet cross-aggregate morphology molecular sieve synthesized in this example has technical superiority.
[0116] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A flower ball-like mordenite, wherein the flower ball-like mordenite is a self-assembled aggregate of a plurality of sheet-like mordenites, wherein: The plurality of sheet-like mordenite zeolites are vertically cross-aggregated with each other to perform the self-assembly, and the 001 crystal planes corresponding to the 12-membered pores of the sheet-like mordenite zeolite are exposed to the outside.
2. The flower-like mordenite according to claim 1, characterized in that: The thickness of the flake-like mordenite is 2 to 200 nm, preferably 5 to 100 nm; and / or, The diameter of the flower-spherical mordenite is 1000-6000 nm, preferably 1200-5000 nm.
3. The flower-like mordenite according to claim 1, characterized in that: The mesopore diameter of the flower-like mordenite is 3 to 200 nm, and the mesopore volume is 0.05 to 0.9 cm 3 / g; Preferably, the mesopore diameter of the flower-like mordenite is 10-20 nm, and the mesopore volume is 0.1-0.6 cm 3 / g; More preferably, the ratio of the mesopore volume to the total pore volume of the flower ball-like mordenite is 40% to 80%.
4. The flower-spherical mordenite according to any one of claims 1 to 3, characterized in that: The specific surface area of the flower-like mordenite is 320 to 865 m 2 / g, external specific surface area 70~610m 2 / g.
5. A method for preparing a flower-spherical mordenite, preferably for preparing the flower-spherical mordenite according to any one of claims 1 to 4, the method comprising: (1) mixing an aluminum source, a structure directing agent 1, an alkali source and water to obtain a mixed system 1; (2) adding a silicon source and a structure directing agent 2 to the mixture 1, and mixing to obtain a mixed system 2; (3) stirring and crystallizing the mixed system 2, and filtering and washing to obtain a crystallized product; (4) performing ion exchange and heat treatment on the crystallized product to obtain the flower ball-like mordenite.
6. The preparation method according to claim 5, characterized in that: The aluminum source is selected from one or more of boehmite, pseudo-boehmite, aluminum hydroxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum isopropoxide; and / or, The silicon source is selected from one or more of silicon oxide, water glass, silica sol, ethyl silicate, sodium silicate, silica gel, and white carbon black; and / or, The alkali source is selected from at least one of sodium hydroxide, liquid alkali, potassium hydroxide and calcium hydroxide.
7. The preparation method according to claim 5, characterized in that: The structure directing agent is selected from aliphatic amine compounds, preferably one or more selected from linear alkylamines, tetraalkylammonium hydroxides, tetraalkylammonium halides, ammonia water, cyclic alkylamines, and alkyl diammonium halides, and more preferably one or more selected from ethylamine, hexylamine, ethylenediamine, hexyldiamine, tetraethylammonium bromide, tetraethylammonium hydroxide, tetramethylammonium bromide, tetramethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium hydroxide, ammonia water, hexamethyleneimine, cyclohexylamine, and hexamethylammonium bromide.
8. The preparation method according to claim 5, characterized in that: The second structure directing agent is selected from: a compound containing at least one benzene ring and at least one amino group, and / or a compound containing at least one benzene ring and at least one quaternary ammonium salt; Preferably, the second structure directing agent is selected from at least one of the compounds represented by formula (I) and / or the compounds represented by formula (II): In formula (I), R1 to R7 are each independently selected from hydrogen, alkyl or aryl, and n is any natural number; preferably, R1 to R7 are each independently selected from hydrogen, C1 to C10 alkyl or benzyl, and n is a natural number of 0 to 10; In formula (II), R 1 ~R 10 Each is independently selected from hydrogen, alkyl or aryl, and m is any natural number; M - is an anion; preferably, R 1 ~R 10 Each is independently selected from hydrogen, C1-C10 alkyl or benzyl, m is any natural number from 0 to 10; M - Cl - Br - ,I - 、F - or OH - ; More preferably, the second structure-directing agent represented by formula (I) is selected from at least one of aniline, methylaniline, dimethylaniline, trimethylaniline, tetramethylaniline, pentamethylaniline, o-ethylaniline, p-ethylaniline, m-ethylaniline, isopropylbenzylamine, benzyldimethylamine, N-benzyltert-butylamine, N-benzyln-butylamine, N-benzylisobutylamine and N-benzylisobutylamine; and / or, the second structure-directing agent represented by formula (II) is selected from at least one of benzyltriethylammonium chloride, benzyltriethylammonium bromide, benzyltriethylammonium chloride, benzyltriethylammonium bromide and benzyltriethylammonium chloride. At least one of ethylammonium fluoride, benzyltriethylammonium hydroxide, benzyltripropylammonium chloride, benzyltripropylammonium bromide, benzyltripropylammonium fluoride, benzyltripropylammonium hydroxide, tetradecyldimethylbenzylammonium bromide, hexadecyldimethylbenzylammonium bromide, dodecyldimethylbenzylammonium bromide, decyldimethylbenzylammonium bromide, decyldimethylbenzylammonium chloride, tetradecyldimethylbenzylammonium chloride, hexadecyldimethylbenzylammonium chloride, and dodecyldimethylbenzylammonium chloride.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The molar ratio of the structure directing agent 1 to the silicon source is 0.001-0.5, the molar ratio of the water to the silicon source is 5-1000 (preferably 5-150), the molar ratio of the alkali source to the silicon source is 0.005-0.5, the molar ratio of the silicon source to the aluminum source is 5-60, and the molar ratio of the structure directing agent 2 to the silicon source is 0.0005-0.5, wherein the molar amount of the aluminum source is calculated as the molar amount of its Al2O3, the molar amount of the alkali source is calculated as the molar amount of its metal oxide (M2O), and the molar amount of the silicon source is calculated as SiO2.
10. The preparation method according to claim 9, characterized in that: Step (3) is carried out in an autogenous crystallization reactor, and preferably, the stirring is carried out for 2 to 8 hours; and / or, In step (3), the crystallization temperature is 130 to 200° C., and the crystallization time is 1 to 48 hours.
11. The flower-spherical mordenite obtained by the preparation method according to any one of claims 5 to 10.
12. A zeolite catalyst comprising mordenite, a binder and a metal component, wherein: The mordenite is selected from the flower-ball-like mordenite described in any one of claims 1 to 4 or the flower-ball-like mordenite obtained by the preparation method described in any one of claims 5 to 10; preferably, the binder is selected from at least one of silica sol, aluminum sol, phosphate aluminum sol, alumina, and pseudo-boehmite; and / or, the metal component is selected from at least one or at least two of platinum, molybdenum, bismuth, tin, cadmium, cobalt, nickel, rhenium, palladium, gallium, ruthenium, and lanthanum.
13. Use of the flower-spherical mordenite according to any one of claims 1 to 4, the flower-spherical mordenite obtained by the preparation method according to claims 5 to 10, or the zeolite catalyst according to claim 12 in aromatic hydrocarbon transalkylation reactions, especially in the conversion of C6 to C12 aromatic hydrocarbons to produce xylene.
Citation Information
Patent Citations
Method for synthesizing mesoporous mordenite
CN102190316A
Preparation method of layered nano-mordenite molecular sieve
CN102718231A
Pillared layered mordenite, and preparation method thereof
CN106517239A
Flaky nano-mordenite molecular sieve synthesis method and mordenite molecular sieve
CN107963637A
Drive system for a vehicle moving along a trackway, particularly a magnetic levitation train
CN1847046A
Cited By
Mordenite molecular sieve as well as preparation method and application thereof
CN121778748A